2022
DOI: 10.1111/ijfs.15931
|View full text |Cite
|
Sign up to set email alerts
|

Pepper‐rosmarin essential oil (Lippia sidoides Cham.) as an antioxidant additive for PBAT – poly (butylene adipate co‐terephthalate) films and its application for active packaging

Abstract: Summary Active antioxidant films additivated with Pepper‐rosmarin essential oil (PRO) and poly (butylene adipate co‐terephthalate) – PBAT were produced from the solvent casting technique in different concentrations (5%, 10%, and 15%) and the antioxidant activity of the film was evaluated by the oxidation of olive oil. Homogenous films were produced and the incorporation of PRO was confirmed by the principal component analysis (PCA) technique. The antioxidant capacity of the PRO analysed indicated high activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…• A positive effect on the freshness of meat was reported [62] Ginger EO The antioxidant activities of the films significantly increased with the addition of ginger EO [29] Pepper-rosmarin The addition of Pepper-rosmarin EO and poly (butylene adipate co-terephthalate) to active packaging film inhibited the oxidation of olive oil [95] Cinnamon EO Increased antioxidant activity of silicon dioxide nanoparticles used in the active packaging [96] Table 3. Incorporation of EOs in active packaging system as antioxidant agent.…”
Section: Essential Oil Antioxidant Effect Of Eo Referencesmentioning
confidence: 99%
“…• A positive effect on the freshness of meat was reported [62] Ginger EO The antioxidant activities of the films significantly increased with the addition of ginger EO [29] Pepper-rosmarin The addition of Pepper-rosmarin EO and poly (butylene adipate co-terephthalate) to active packaging film inhibited the oxidation of olive oil [95] Cinnamon EO Increased antioxidant activity of silicon dioxide nanoparticles used in the active packaging [96] Table 3. Incorporation of EOs in active packaging system as antioxidant agent.…”
Section: Essential Oil Antioxidant Effect Of Eo Referencesmentioning
confidence: 99%
“…Rosemary essential oil was used to prepare PBAT active antioxidant films as an active packaging material by solvent casting technology, which can minimize the oxidation of food and ensure their quality. 34 PBAT film after incorporating curcumin showed effective antioxidant and antibacterial activity, and its water vapor barrier was improved. 35 The composite films after the addition of quercetin into PBAT/ thermoplastic starch through extrusion blow molding, showed enhanced antioxidant and UV resistance, with an oxygen barrier of up to 94%.…”
Section: Introductionmentioning
confidence: 98%
“…Several works have been reported on the antioxidant modification of PBAT by natural substances. Rosemary essential oil was used to prepare PBAT active antioxidant films as an active packaging material by solvent casting technology, which can minimize the oxidation of food and ensure their quality 34 . PBAT film after incorporating curcumin showed effective antioxidant and antibacterial activity, and its water vapor barrier was improved 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are the natural source of ingredients in foodstuffs (Kose & Ocak, 2018). Most studies have shown that phenolic compounds in plants contribute significantly to their antioxidant capacity (Cai et al ., 2004; Wu et al ., 2023; Shan et al ., 2007; de Andrade et al ., 2022). Some studies have shown that phenolic compounds found in plants may also play a characteristic as antimicrobial role (Hara‐Kudo et al ., 2004; Huang et al ., 2023; Wu et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%